Role of serum hepcidin in neonatal sepsis detection: a systematic review - Citra Yulia Sari; Selia Cahyani; Pisi Nopita Wigati; ,Muhammad Sidiq; Basra Ahmad Amru; Almerveldy Azaria Dohong; Farah Elena; Masayu Amanda Ledika (Indonesian Pediatric Society, 2026)
Background Neonatal sepsis is a severe, life-threatening condition and major cause of infant mortality, especially in developing nations. Diagnosing newborn sepsis presents significant challenges due to the nonspecific symptoms. While blood cultures serve as the diagnostic gold standard, they exhibit lengthy processing times and inconsistent reliability. Hepcidin, an iron-regulating hormone with antimicrobial properties, is increasingly recognized as a promising early sepsis biomarker in neonates. Objective The objective of this study is to evaluate the diagnostic performance of serum hepcidin through a systematic review of the literature. Methods Following PRISMA protocols, PubMed, ScienceDirect, SAGE Journals, ClinicalTrials.gov, and Google Scholar were systematically searched for relevant studies conducted from 2010-2025. Observational studies assessing hepcidin levels in septic neonates were examined, with emphasis on diagnostic metrics including the Area Under the Receiver Operating Characteristic Curve (AUC), sensitivity, specificity, Positive Predictive Value (PPV), and Negative Predictive Value (NPV). Study selection and risk-of-bias assessment were conducted independently by two reviewers using the Joanna Briggs Institute criteria. Results Among 3,047 screened publications, four studies using case-control and prospective cohort designs, comprising 481 neonates, were included. Hepcidin diagnostic thresholds for septic newborns ranged between 92-105 ng/mL, with AUC values of 0.79-0.93. Sensitivity reached 100% maximum, specificity peaked at 94%, and both PPV and NPV ranged from 87-95%. Conclusion Serum hepcidin has been identified as an early biomarker for neonatal sepsis, exhibiting diagnostic accuracy. Despite these findings, further validation and methodological standardization are essential before widespread clinical adoption